An Analysis of Seventh Grade Students' English-Speaking Difficulties - Ahmad Thoyyib Shofi dan Fina Rizqiyyatul Hikmah (Jurnal Ilmu Pendidikan Islam, 2022)
Among the four language skills, speaking ability is one of the most crucial. It is believed to be an indicator of competency in a language. (Zulaikah, 2019) considers the speaking skill to be the most important of the four language abilities, and EFL students should master it. Sadly, most students learning English as a foreign language are good at reading and writing, but they have difficulty in speaking (Karim, 2020). Hence, this research was to analyse the difficulty of speaking English. This research used a qualitative-descriptive research design. A total of 22 seventh-grade students were purposively selected and participated in this research. The researcher used two instruments to gather data: tests and questionnaires. The findings show that the speaking difficulties faced by the students are classified into two types: psychological and linguistic. Psychological difficulty includes a lack of motivation, a lack of confidence, hesitancy and fear of being wrong when speaking, and the perception that speaking English is difficult. Linguistic difficulty includes a lack of vocabulary, pronunciation errors, and poor grammar proficiency. Besides, students were also affected by the following factors when they tried to speak English: First, 41% are inhibition; 23% are nothing to say; 18% speak Javanese; 14% prefer silence; and 4% have poor listening ability. Keywords: Speaking difficulty, Factors affecting speaking fluency.